Low‐Dose Cone‐Beam Computed Tomography in Swedish Pediatric Patients With Alveolar Clefts Following Alveolar Bone Grafting—A Clinical Study - António Vicente; Josefine Cederhag; Nilofar Rashidi; Anna‐Paulina Wiedel; Magnus Becker; Susanne Brogårdh‐Roth; Xie‐Qi Shi; Kristina Hellén‐Halme (Clinical and Experimental Dental Research)
ABSTRACT Objectives The aim of this study was to investigate whether a low‐dose cone‐beam computed tomography (CBCT) protocol provides diagnostically acceptable image quality for assessing bone healing after alveolar bone grafting. Material and Methods The study cohort comprised 11 patients (aged 7–14 years) with orofacial clefts who had undergone alveolar bone grafting at Skåne University Hospital in Malmö, Sweden. During the postsurgical follow‐up at 6 months, each patient was assessed twice: once with a standard‐dose CBCT protocol and once with a low‐dose CBCT protocol, which in total corresponds to one CBCT examination made with the exposure settings recommended by the manufacturer. Among others, the assessed parameters included subjective image quality, as well as bone graft height, thickness, and integration. Results No significant differences were found between the standard‐ and low‐dose protocols for most parameters (p > 0.05). Exceptions included subjective image quality (one observer, p = 0.05) and confidence levels during the assessment (three observers, p = 0.01, 0.01, 0.02). Conclusions The low‐dose protocol yielded adequate image quality for postoperative CBCT healing assessment in patients who have undergone alveolar bone grafting. However, the confidence level of observers during the assessment with the low‐dose protocol was reduced. This study is registered on ClinicalTrials.gov (NCT06395077). Clinical Trial Registration This study is registered on ClinicalTrials.gov (NCT06395077).